2017
DOI: 10.1002/btpr.2538
|View full text |Cite
|
Sign up to set email alerts
|

High yield process for the production of active human α‐galactosidase a in CHO‐K1 cells through lentivirus transgenesis

Abstract: Fabry disease is an X-linked recessive disorder caused by a deficiency in lysosomal α-Galactosidase A. Currently, two enzyme replacement therapies (ERT) are available. However, access to orphan drugs continues to be limited by their high price. Selection of adequate high-expression systems still constitutes a challenge for alleviating the cost of treatments. Several strategies have been implemented, with varying success, trying to optimize the production process of recombinant human α-Galactosidase A (rhαGAL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…We could confirm that the position of the fucose is the outer, not the core, by a diagnostic ion at m / z 512.190 [HexHexNAcFuc + H] + . The presence of NeuGc in therapeutic lysosomal enzymes has been reported in previous studies, , but the detailed glycan structure was first revealed in this study.…”
Section: Resultsmentioning
confidence: 60%
“…We could confirm that the position of the fucose is the outer, not the core, by a diagnostic ion at m / z 512.190 [HexHexNAcFuc + H] + . The presence of NeuGc in therapeutic lysosomal enzymes has been reported in previous studies, , but the detailed glycan structure was first revealed in this study.…”
Section: Resultsmentioning
confidence: 60%
“…The increasing incidence of certain cancers and viral hepatitis has increased the demand for rhIFN-α2b, suggesting that rhIFN-α2b must be optimized in all the expression systems used for its production [22]. Although many mammalian expression systems can undergo posttranscriptional modification, Chinese hamster ovary (CHO) expression system was considered as the preferred production platform for the expression of proteins that require posttranslational modification, because it has the following advantages: the expressed proteins are closest to natural proteins in terms of molecular structure, physicochemical properties and biological functions; CHO cells can grow at high density in suspension culture under serum-free culture conditions; protein products can be secreted extracellularly, facilitating downstream protein purification [25]. For the above reasons, we chose the CHO system to express IFN.…”
Section: Discussionmentioning
confidence: 99%